A Difficult Case of Ventriculitis in a 40-Year-Old Woman with Acute Myeloid Leukemia - Raffaella Rubino; Marcello Trizzino; Luca Pipitò; Giuseppe Sucato; Marco Santoro; Rosario Maugeri; Domenico Gerardo Iacopino; Giovanni Maurizio Giammanco; Sergio Siragusa; Antonio Cascio (MDPI AG, 2024)
Ventriculitis and nosocomial meningitis caused by carbapenem-resistant Gram-negative and vancomycin-resistant Gram-positive bacteria represent a growing treatment challenge. A case of ventriculitis and bacteremia caused by carbapenem-resistant, KPC-producing Klebsiella pneumoniae and vancomycin-resistant Enterococcus faecium in a young woman with acute leukemia who was successfully treated with meropenem/vaborbactam (MVB), rifampicin, and linezolid is described in this paper. This case report emphasizes the importance of a multidisciplinary strategy, including infectious focus control, for the treatment of device-associated central nervous system (CNS) infections from multidrug-resistant bacteria. Considering the novel resistance patterns, more research on drug penetration into the central nervous system, as well as on the necessity of association therapies, is needed.